Kansas Corn Rootworm Areawide Management Program Using Semiochemicals - Sloderbeck, Phil; Higgins, Randall; Wilde, Gerald; Shufran, Roxanne; Whitworth, Jeff; Yan Zhu, Kun; Buschman, Larry (My University, 1998)
This publication describes corn rootworms and how to manage them.
MF2369_1998_11
Keywords: MF2369; Crops; Insects; MF